The effectiveness of the combination of nature sound and foot massage against pain post-appendectomy patients - Setyowati, Anita; Ta'adi, Ta'adi; Sulistyowati, Dina Indrati Dyah (Media Keperawatan Indonesia, 2023)
Appendectomy is done as soon as possible to reduce the risk of further perforation such as peritonitis or abscess. If not handled properly it can cause complications, slow down the recovery process, and increase the length of hospital stay. The purpose of the study is to analyze the effectiveness of the combination of nature sound and foot massage on pain in post-appendectomy patients. Method: True experiment with pre-post test control group design. The intervention group (n=21) was given nature sound therapy for 15 minutes, the combination group (n=21) was given a combination of nature sound therapy and foot massage for 15 minutes, and the control group (n=21) received routine nursing care. Data analysis used the Wilcoxon test. Results: The combination of nature sound and foot massage for 15 minutes/day is effective and significantly reduces pain on the average Numeric Rating Scale (NRS) score. There were differences in pain before and after the intervention in the three groups. Combination therapy of nature sound and foot massage has a greater value than the hospital SPO group and the nature sound group with a p-value of 0.004 and delta a mean of 0.70. In conclusion: The combination of nature sound and foot massage is effective in reducing pain in post-appendectomy patients.